2015
DOI: 10.1111/bju.13249
|View full text |Cite
|
Sign up to set email alerts
|

Urinary fistula after robot‐assisted partial nephrectomy: a multicentre analysis of 1 791 patients

Abstract: ObjectiveTo evaluate the incidence of and risk factors for a urine leak in a large multicentre, prospective database of robot-assisted partial nephrectomy (RPN). Patients and MethodsA database of 1 791 RPN from five USA centres was reviewed for urine leak as a complication of RPN. Patient and tumour characteristics were compared between patients with and those without postoperative urine leaks. Fisher's exact test was used for qualitative variables and Wilcoxon sum-rank tests were used for quantitative variabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
13
0
7

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(22 citation statements)
references
References 65 publications
2
13
0
7
Order By: Relevance
“…In fact, higher nephrometry scores and complexity were related to pelvicalyceal system entry/repair. Potretzke et al [77] conducted a review of studies on urinary fistula after robotic PN, and found that pelvicalyceal system entry and tumor size were related to the development of urine leak. These two parameters could be interpreted as a reflection of tumor complexity, which could be the reason for urinary fistula incidence.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, higher nephrometry scores and complexity were related to pelvicalyceal system entry/repair. Potretzke et al [77] conducted a review of studies on urinary fistula after robotic PN, and found that pelvicalyceal system entry and tumor size were related to the development of urine leak. These two parameters could be interpreted as a reflection of tumor complexity, which could be the reason for urinary fistula incidence.…”
Section: Discussionmentioning
confidence: 99%
“…The incidence of urine leakage in OPN is reported to range from 1.0 to 17.4%; this incidence is higher than that in minimally invasive partial nephrectomy because of the indication for relatively hilar-located tumors in OPN ( 24 ). Urine leakage occurs if the collecting system opens during the resection of hilar tumors and is not fully repaired.…”
Section: Discussionmentioning
confidence: 99%
“…Other risk factors for hemorrhagic complications are high American Society of Anesthesiologists (ASA) scores and smoking [25]. The incidence of urinary fistula after partial nephrectomy has ranged from 1% to 17.4% [26]. However, more recent studies report urinary leakage rates between 0.6% and 3% [27,28].…”
Section: Discussionmentioning
confidence: 99%
“…However, more recent studies report urinary leakage rates between 0.6% and 3% [27,28]. Risk factors include hilar tumor location, tumor size, blood loss, and need for pelvicalyceal repair [26,2931]. …”
Section: Discussionmentioning
confidence: 99%